Composite current collector and preparation method thereof, electrode plate and battery
By preparing a ceramic base layer and plating a metal layer on the base film layer of the composite fluid collection, the problems of poor adhesion and poor water vapor barrier properties are solved, and the safety and production efficiency of the battery are significantly improved.
Patent Information
- Application Number
- CN202411902197.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The existing composite liquid collector has poor adhesion and poor water vapor barrier properties when the battery is short-circuited, resulting in insufficient battery safety.
By preparing a ceramic base layer on the base film layer and plating a metal layer thereon, magnetron sputtering technology and ion implantation method are used to improve the bonding force and water vapor barrier between the base film layer and the metal layer.
It significantly improves the adhesion and water vapor barrier properties of the composite fluid collection, and enhances the safety and production efficiency of the battery.
Smart Images

Figure CN119685779A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite current collector and a preparation method thereof, an electrode sheet and a battery. Background Art
[0002] With the rapid development of the global new energy industry, lithium-ion batteries are widely used in energy storage and automobile fields due to their high energy density and good cycle performance. However, the frequent occurrence of accidents such as battery fires has made lithium-ion battery safety issues the most basic demand for battery products, among which internal short circuits in batteries are the most important cause of safety problems. For power batteries, external stresses such as collisions and extrusions are one of the main causes of battery short circuits and fires.
[0003] The new composite current collector has a multi-layer composite structure of "polymer substrate intermediate layer + thin conductive metal layer". When a short circuit occurs in the battery, it can provide a large resistance through fusing and insulation to cut off or reduce the short-circuit current in a short time, effectively preventing thermal runaway of the battery and improving battery safety.
[0004] Composite metal current collector substrates often use organic polymer material base film layers such as PET / PP, and use a winding coating process to achieve copper, aluminum or other metal plating. Among them, there are also problems such as poor adhesion and poor water vapor barrier properties. The main reasons are: on the one hand, metal atoms cannot be well embedded in the organic polymer base film, and on the other hand, it is difficult to form a covalent bond between the base film layer and the surface of the organic polymer base film, so the adhesion between the metal and the base film layer is poor; and because the organic polymer material itself has poor water vapor barrier properties, water vapor can easily penetrate through the gaps in the organic polymer base film layer to the bottom of the metal coating.
[0005] These problems are particularly evident for composite aluminum current collectors prepared by evaporation coating. In order to enhance the adhesion between the base film layer and the metal layer in the composite aluminum current collector, an ion source is usually added before evaporation coating, and argon gas Ar is introduced. The high voltage electric field generated by the DC power supply and the magnetic field generated by the magnetic bar inside the ion source are used to ionize the argon gas Ar to generate Ar. + , high energy ion Ar + Bombarding the base film layer can remove free organic volatiles in the base film layer, thereby improving the bonding strength between metal aluminum and the base film layer, but the effect of this method is limited. Summary of the invention
[0006] The object of the present invention is to provide a composite current collector and a preparation method thereof, an electrode sheet and a battery in view of the above problems.
[0007] The technical solution provided by the present invention is:
[0008] The first aspect of the present application provides a method for preparing a composite current collector, comprising the following steps: preparing a ceramic primer layer on a base film layer by magnetron sputtering, and plating a metal layer on the ceramic primer layer;
[0009] When preparing the ceramic base layer, inert gas and active gas are introduced at the same time. The two are ionized under a high voltage electric field. After the inert gas is ionized, it bombards the metal target to form metal atoms. After the active gas is ionized, it combines with the metal atoms and is deposited on the surface of the base film layer to form a ceramic base layer.
[0010] In order to optimize the above technical solutions, the specific limitations adopted also include:
[0011] The inert gas is selected from at least one of helium, argon or rare gas; the active gas is selected from at least one of oxygen and nitrogen.
[0012] After ionization occurs under a high voltage electric field, the inert gas loses electrons to form positive ions, and the active gas gains electrons to form negative ions.
[0013] Before preparing the ceramic base layer, the surface of the base film layer is treated by ion implantation.
[0014] The ion implantation method is used to treat the surface of the base film layer by introducing an inert gas, or by introducing an inert gas and an active gas at the same time.
[0015] The second aspect of the present application provides a composite current collector, including a base film layer, a base layer outside the base film layer and a metal layer outside the base layer; the base layer is a ceramic base layer; the main component of the ceramic base layer includes at least one of metal oxides and metal nitrides.
[0016] Covalent bonds are formed between the metal atoms of the metal layer and the ceramic material of the ceramic base layer.
[0017] A covalent bond is formed between the ceramic material of the ceramic primer layer and the base film material of the base film layer.
[0018] The third aspect of the present application provides an electrode sheet, comprising the composite current collector provided in the second aspect of the present application.
[0019] The fourth aspect of the present application provides a battery, comprising the electrode sheet provided in the third aspect of the present application.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention provides a composite current collector and a preparation method thereof. A ceramic base layer is arranged between a base film layer and a metal layer. The ceramic base layer can enhance the bonding strength with the base film layer and can effectively block the water vapor of the base film layer, thereby improving the adhesion of the composite current collector and ensuring high production efficiency.
[0022] The present invention also provides a method for preparing a composite current collector, wherein a ceramic base layer is prepared on a base film layer, and a metal layer is plated on the ceramic base layer. When preparing the ceramic base layer, the present invention preferably adopts magnetron sputtering technology, and simultaneously introduces an inert gas and an active gas, wherein the inert gas and the active gas are ionized under a high voltage electric field, and the inert gas bombards a metal target material to form metal atoms after ionization, and the active gas is ionized and combined with the metal atoms through covalent bonds to form a ceramic material deposited on the surface of the base film layer to form a ceramic base layer; and when the metal layer is subsequently prepared, since the metal atoms of the metal layer are easy to generate covalent bonds with the ceramic material of the ceramic base layer, the bonding force between the base layer and the metal layer can be enhanced, thereby further improving the overall adhesion of the composite current collector.
[0023] Before preparing the ceramic base layer, the present invention also treats the surface of the base film layer by ion implantation, ionizes the gas by a high-voltage electric field to form a high-energy ion beam, and bombards the surface of the base film layer; preferably, a method of simultaneously introducing an inert gas and an active gas is adopted, in which the inert gas can clean the surface of the base film layer, and when the active gas bombards the surface of the base film layer, the high-energy ions combine with the molecules of the base film layer to form stable covalent bonds, and when the ceramic base layer is prepared later, the high-energy ions can form covalent bonds with the metal atoms, so that the base film layer and the base film layer are stably bonded. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 : A schematic flow chart of a preferred embodiment of the composite current collector preparation method of the present invention. DETAILED DESCRIPTION
[0025] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.
[0026] The experimental methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the technical field unless otherwise specified.
[0027] The present application provides a method for preparing a composite current collector, comprising the following steps: preparing a ceramic base layer on a base film layer, and plating a metal layer on the ceramic base layer.
[0028] Preferably, a ceramic primer layer is prepared on the base film layer by magnetron sputtering. When preparing the ceramic primer layer, an inert gas and an active gas are introduced simultaneously, and the two are ionized under a high voltage electric field. After the inert gas is ionized, it bombards the metal target material to form metal atoms, and after the active gas is ionized, it combines with the metal atoms and is deposited on the surface of the base film layer to form the ceramic primer layer.
[0029] Preferably, the inert gas is selected from at least one of helium, argon or a rare gas.
[0030] Preferably, the active gas is selected from at least one of oxygen and nitrogen.
[0031] After ionization occurs under a high voltage electric field, the inert gas loses electrons to form positive ions, and the active gas gains electrons to form negative ions.
[0032] After being ionized, the inert gas bombards the metal target to form metal atoms. After being ionized, the active gas combines with the metal atoms through covalent bonds to form a ceramic material that is deposited on the surface of the base film layer to form a ceramic base layer.
[0033] When the metal layer is subsequently prepared, the metal atoms of the metal layer can easily form covalent bonds with the ceramic material of the ceramic base layer, which can further enhance the bonding force between the base layer and the metal layer, thereby improving the overall adhesion of the composite current collector.
[0034] In some embodiments, before preparing the primer layer on the base film layer by magnetron sputtering, the surface of the base film layer is treated by ion implantation.
[0035] In treating the surface of the base film layer by ion implantation, the selection range of the inert gas and the active gas is the same as the selection range of the inert gas and the active gas in preparing the base layer by magnetron sputtering, that is, the inert gas is selected from at least one of helium, argon or a rare gas; the active gas is selected from at least one of oxygen and nitrogen.
[0036] The ion implantation method is used to treat the surface of the base film layer by introducing an inert gas; or, the ion implantation method is used to clean the surface of the base film layer by simultaneously introducing an inert gas and an active gas. This method is the preferred option. The inert gas can clean the surface of the base film layer, and the active gas combines with the molecules of the base film layer to form stable covalent bonds when bombarding the surface of the base film layer. When the magnetron sputtering technology is used to prepare the ceramic base layer, covalent bonds are formed with the metal atoms to ensure a stable bond between the base film layer and the base film layer.
[0037] Preferably, the ion implantation method in the present application adopts a Hall ion source, and the specific parameters are as follows:
[0038] When the inert gas and active gas are introduced to clean the surface of the base film layer, the flow rate selection range of the inert gas is: 70-120sccm, and the flow rate selection range of the active gas is: 200-400sccm.
[0039] The processing time range of the base film layer is: 0.2-0.5s; the base film winding speed range is 180-480m / min.
[0040] Hall ion source power voltage: 200-300V, current: 3-7A.
[0041] In some embodiments, the ceramic primer layer is prepared on the base film layer by magnetron sputtering, and the specific working parameters that can be used are as follows:
[0042] The base film winding speed range is: 200-300m / min;
[0043] Al Target Power:2*15kw.
[0044] The flow rate of injected gas in magnetron sputtering is:
[0045] The flow rate selection range of the inert gas is: 70-120sccm, and the flow rate selection range of the active gas is: 200-400sccm.
[0046] The method for preparing the metal layer on the base layer can be selected from vacuum evaporation, chemical deposition, magnetron sputtering or water electroplating, or a combination of more than one of them.
[0047] The present application also provides a composite current collector, including a base film layer, a base layer outside the base film layer, and a metal layer outside the base layer; the base layer is a ceramic base layer.
[0048] Wherein, the main component of the ceramic primer layer includes at least one of metal oxide and metal nitride.
[0049] A covalent bond is formed between the ceramic material of the ceramic primer layer and the base film material of the base film layer.
[0050] Covalent bonds are formed between the metal atoms of the metal layer and the ceramic material of the ceramic base layer.
[0051] In some embodiments, the metal layer is an aluminum metal layer, and the main component of the ceramic primer layer includes at least one of aluminum oxide and aluminum nitride.
[0052] The present application also provides an electrode sheet comprising the above-mentioned composite current collector.
[0053] The present application also provides a battery, comprising the above-mentioned electrode sheet.
[0054] For the sake of simplicity, this document only specifically discloses some numerical values and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.
[0055] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.
[0056] The present invention is further described in detail below in conjunction with specific embodiments:
[0057] Example 1
[0058] The existing composite metal current collectors have problems such as poor adhesion and poor water vapor barrier properties. The preparation of a more obvious composite aluminum current collector is used as an example as follows:
[0059] Most composite aluminum current collectors are produced by evaporation coating, but the composite aluminum current collectors produced by evaporation coating still have problems such as poor adhesion and poor water vapor barrier properties: the kinetic energy of aluminum vapor molecules is low, and at the microscopic level, aluminum atoms cannot be well embedded in the base film layer; it is difficult for metal aluminum atoms to form covalent bonds with the surface of the base film layer, resulting in poor adhesion between the base film layer and the metal; since the base film layer itself has poor water vapor barrier properties, water vapor can easily penetrate through the gaps in the base film material to the bottom of the aluminum coating layer, resulting in poor water vapor barrier properties of the composite aluminum current collector, causing the adhesion to further decrease.
[0060] This embodiment improves the problem of poor adhesion and poor water vapor barrier of the composite aluminum current collector by the following steps:
[0061] (1) Treatment of PET base film:
[0062] Before evaporating the metal coating, 200 sccm oxygen and 100 sccm nitrogen were introduced into the Hall ion source, the base film layer was treated for 0.5 s, and the winding speed was 240 m / min;
[0063] In this step, the high voltage electric field generated by the Hall ion source is used to ionize oxygen O2 and nitrogen N2. The ionized oxygen ions and nitrogen ions are continuously accelerated to form ion beams under the magnetic field of the Hall ion source. - 、N - ) bombards the surface of the organic material PET base film.
[0064] (2) Preparation of ceramic base layer:
[0065] The ceramic base layer was prepared by magnetron sputtering technology using a pulsed DC power supply, wherein the argon flow rate was 100 sccm, the oxygen flow rate was 200 sccm, and the winding speed was 240 m / min;
[0066] In this step, argon Ar and oxygen O2 are ionized to produce stable sputtering argon ions Ar + and oxygen ions O - , where Ar + Under the combined action of high-voltage electric and magnetic fields, the ions collide with the cathode aluminum target at high speed, sputtering Al atoms to fly toward the organic material PET at high speed. Under the action of high-voltage electric and magnetic fields, the O- ions fly toward the organic material PET at high speed in the opposite direction. In this process, they collide and combine with Al atoms to form aluminum oxide and embed into the PET surface at high speed. Some of the Al atoms fly toward the surface of the organic material PET at high speed and collide with the oxygen ions O injected in the first step. - 、Nitrogen ion N - Combined to form aluminum oxide Al x O x 、Aluminum Nitride Al x N x , forming a ceramic material layer.
[0067] (3) Preparation of aluminum metal coating:
[0068] A metal aluminum coating was prepared by vacuum evaporation, wherein the coating speed was 240 m / min, the wire feeding speed was 480 m / min, and the aluminum film thickness was 1 μm;
[0069] In this step, the aluminum atoms Al produced by evaporation and aluminum oxide Al x O x 、Aluminum Nitride Al x N x It is easy to produce metal covalent bonds, that is, the aluminum layer Al and the aluminum oxide Al x O x 、Aluminum Nitride Al x N x The bonding strength is high, thereby improving the overall adhesion.
[0070] Embodiment 2:
[0071] The preparation method is exactly the same as that of Example 1, except that the PET base film is not treated.
[0072] Example 3: The preparation method is exactly the same as that of Example 1, except that only inert gas (non-active gas) is used to treat the base film.
[0073] Embodiment 4:
[0074] The preparation method is exactly the same as that in Example 1, except that the ceramic base layer is replaced by a vacuum evaporation method to prepare an aluminum oxide coating as the base layer.
[0075] Comparative Example 1:
[0076] The preparation method is exactly the same as that of Example 1, except that the PET base film is not treated, and the preparation of the ceramic base layer is replaced by the preparation of an aluminum oxide coating as the base layer by vacuum evaporation.
[0077] Table 1 Experimental results of examples and comparative examples
[0078]
[0079] From the test results of each embodiment and comparative example, it can be seen that:
[0080] The effect of Example 1 is significantly better than that of other examples and comparative examples. By preparing the ceramic base layer through magnetron sputtering technology, a certain thickness of ceramic material can be stably deposited on the surface of the base film layer, which not only ensures the bonding performance of the metal plating, but also ensures the water vapor barrier ability of the base film layer.
[0081] Furthermore, the surface of the base film layer is treated by an ion implantation method in which an inert gas and an active gas are simultaneously introduced, and then a ceramic base layer is prepared by magnetron sputtering technology. The combination of these two steps can significantly improve the bonding strength of the coating, and even if metal is plated by evaporation plating, high-efficiency coating formation can be guaranteed; and when treating the surface of the base film layer, introducing an inert gas and an active gas at the same time has a better effect than introducing only an inert gas.
[0082] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing a composite current collector, characterized in that: The following steps are involved: A ceramic base layer is prepared on the base film layer by magnetron sputtering, and a metal layer is plated on the ceramic base layer; When preparing the ceramic base layer, inert gas and active gas are introduced at the same time. The two are ionized under a high voltage electric field. After the inert gas is ionized, it bombards the metal target to form metal atoms. After the active gas is ionized, it combines with the metal atoms and is deposited on the surface of the base film layer to form a ceramic base layer.
2. The method for preparing a composite current collector according to claim 1, characterized in that: The inert gas is selected from at least one of helium, argon or rare gas; the active gas is selected from at least one of oxygen and nitrogen.
3. The method for preparing a composite current collector according to claim 1, characterized in that: After ionization occurs under a high voltage electric field, the inert gas loses electrons to form positive ions, and the active gas gains electrons to form negative ions.
4. The method for preparing a composite current collector according to claim 1, characterized in that: Before preparing the ceramic base layer, the surface of the base film layer is treated by ion implantation.
5. The method for preparing a composite current collector according to claim 4, characterized in that: The ion implantation method is used to treat the surface of the base film layer by introducing an inert gas, or by introducing an inert gas and an active gas at the same time.
6. A composite current collector prepared by the method according to any one of claims 1 to 5, characterized in that: It includes a base film layer, a primer layer outside the base film layer and a metal layer outside the primer layer; the primer layer is a ceramic primer layer; the main component of the ceramic primer layer includes at least one of metal oxides and metal nitrides.
7. The composite current collector according to claim 6, characterized in that: Covalent bonds are formed between the metal atoms of the metal layer and the ceramic material of the ceramic base layer.
8. The composite current collector according to claim 6, characterized in that: A covalent bond is formed between the ceramic material of the ceramic primer layer and the base film material of the base film layer.
9. An electrode sheet, characterized in that: A composite current collector comprising any one of claims 6 to 8.
10. A battery, characterized in that: The electrode sheet comprising claim 9.